2012
DOI: 10.1177/0363546512465072
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Landmarks for Tunnel Positioning in Posterior Cruciate Ligament Reconstructions

Abstract: This study established a set of clinically relevant radiographic guidelines for anatomic reconstruction of the PCL. The parameters set forth in this study can be used in both the intraoperative and postoperative settings for both single- and double-bundle PCL reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 35 publications
6
109
0
2
Order By: Relevance
“…First, our specimen sample was relatively small but no smaller than in other radiographic studies with similar methodologies. 12,17,18,23 Additionally, our measurements were quantitative and were applied to hips of variable sizes. In an attempt to address this discrepancy and to increase clinical relevance, both quantitative and qualitative descriptions of all landmarks were provided.…”
Section: Discussionmentioning
confidence: 99%
“…First, our specimen sample was relatively small but no smaller than in other radiographic studies with similar methodologies. 12,17,18,23 Additionally, our measurements were quantitative and were applied to hips of variable sizes. In an attempt to address this discrepancy and to increase clinical relevance, both quantitative and qualitative descriptions of all landmarks were provided.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research focused either on biomechanical laboratory testing or on functional outcome. Even though these reports specified tunnel positions to be anatomic, their intra-articular accurate aperture is rarely demonstrated despite the availability of radiomorphometric data that Medians with ranges and frequencies correlate anatomy and postoperative imaging [14,20,26,27]. A controlled laboratory study by Markolf et al [25] revealed that normal PCL force profiles for most modes of loading are produced with an anterolateral femoral tunnel, whereas a posteromedial and central tunnel position yielded significant increases in graft forces.…”
Section: Discussionmentioning
confidence: 99%
“…This might be one reason for similar group results without statistically significant differences. Nevertheless, tunnels were accepted to be anatomic if they matched the defined radiographic recommendations in the literature [14,20,26,27]. The important role of the replication of anatomic footprints has been elucidated [5,25,28,31,32], but the clinical effect remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations